A systematic review of school-based intervention studies for the prevention or reduction of excess weight among Chinese children and adolescents - Li, M.; Li, S.; Baur, L.; Huxley, Rachel (Wiley-Blackwell Publishing Ltd., 2008)
The aim of this paper was to conduct a systematic review of intervention studies in China aimed at the prevention or control of excess weight gain among children and adolescents. Two Chinese databases (The China Full Text Database and Wanfang Database) and two English databases (Medline and Meditext) were searched with keywords for intervention studies published between 1990 and 2006. Data were extracted on aspects of study quality, methodology and effectiveness of interventions. Quality assessment was conducted using a previously established assessment tool. Twenty-two studies were included, of which 17 were conducted among overweight and/or obese children and/or adolescents. Interventions strategies varied across studies but the majority focused on improving the level of knowledge, physical activity levels and/or diet of overweight children and adolescents. Most studies reported a beneficial effect of the intervention with one or more of the study outcomes, but all of the studies had serious, or moderate, methodological weaknesses. None of the trials identified by this systematic review demonstrated convincing evidence of the efficacy of any single intervention for the prevention of overweight and obesity in children and adolescents from Mainland China. Future intervention trials should address the methodological weaknesses identified in this review. © 2008 The Authors.